Profiles and distribution patterns of different metal Ion contaminants in the sandy soil landfill areas - Mohd Latiff, Nur Hanie; Wan Sulaiman, Wan Syibrah Hanisah; Ramya, Razanah; Mohd Hatta, Farah Ayuni; Othman, Rashidi (Nova Science Publishers, Inc., 2023)
The soil in landfills is contaminated by a variety of unintentionally dumped waste materials, predominantly inorganic, macro, and micro-contaminants. The length, nature, and degree of reactivity of the soil-contaminant system have an impact on its geotechnical properties. Pollutants (such as fertilizers, oils, and landfill leachate) and soil interact physically or chemically, changing the properties of the soil significantly. Therefore, the current study examines the distribution of landfill pollution in sandy soil. To evaluate the profile and distribution pattern of heavy metals in the sandy soil from the upper to deeper layers, soil samples that represented the 10 heavy metal ions (i.e., Al, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) were collected from 4 different closed sanitary and non-sanitary landfills in Perak at varying radii (5-10 m, 10-15 m, and 15-20 m) and depths (0-30 cm, 30-60 cm, and 60-90 cm). The ICP-MS (Perkin Elmer NexION 300X) technique was used to analyse the data. The results indicated that Al and Fe ions were found at higher concentrations in most of the sites, with varying depths and radii having an impact on concentrations. In most locations, the deeper soils were seen to be consistently more contaminated than the top soil layers.